ANALISIS DAMPAK PERUBAHAN SISTEM PERPAJAKAN CORETAX TERHADAP TINGKAT PEMAHAMANAN WAJIB PAJAK DI KABUPATEN ENDE - Herlina Theodensia D. Doke; Jamu, Maria Endang (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to analyze the impact of digitalization changes in tax payment and reporting, which have resulted in delays in tax payment and reporting, leading to fines or penalties for taxpayers. The changes in tax digitalization, which originally started with the e-SPT, E-Filling, and DJP Online applications, and now include Coretax, are information technology systems used by the government to manage taxes digitally. The purpose of Coretax is to improve accuracy, efficiency, and ease of tax reporting. Coretax is expected to reduce leakage and increase tax compliance. In addition, Coretax is expected to streamline the tax administration business process by improving the tax database. Coretax is also a centralized taxation application that can be accessed by taxpayers according to their respective needs. However, in some cases, the implementation of Coretax has been hampered by several factors, such as inaccurate schedules, lack of coordination between teams, and inadequate risk management. These obstacles have resulted in a lack of understanding among taxpayers regarding their tax obligations. The method used in this study was a quantitative approach with case studies. The data collection technique used was a questionnaire, with 384 respondents from various educational and occupational backgrounds. The results showed that the level of taxpayer understanding was still relatively low, which was an impact of the change in the tax payment system using Coretax